Medical applications of Cu, Zn, and S isotope effects. Issue 10 (11th August 2016) - Albarede, Francis; Télouk, Philippe; Balter, Vincent; Bondanese, Victor P.; Albalat, Emmanuelle; Oger, Philippe; Bonaventura, Paola; Miossec, Pierre; Fujii, Toshiyuki
Abstract : Natural isotopic variations of metals in human blood and tissues turn out to be potent biomarkers of pathologies. Abstract : This review examines recent applications of stable copper, zinc and sulfur isotopes to medical cases and notably cancer. The distribution of the natural stable isotopes of a particular element among coexisting molecular species varies as a function of the bond strength, the ionic charge, and the coordination, and it also changes with kinetics. Ab initio calculations show that compounds in which a metal binds to oxygen- (sulfate, phosphate, lactate) and nitrogen-bearing moieties (histidine) favor heavy isotopes, whereas bonds with sulfur (cysteine, methionine) favor light isotopes. Oxidized cations ( e.g., Cu(ii )) and low coordination numbers are expected to favor heavy isotopes relative to their reduced counterparts (Cu(i )) and high coordination numbers. Here we discuss the first observations of Cu, Zn, and S isotopic variations, three elements closely related along multiple biological pathways, with emphasis on serum samples of healthy volunteers and of cancer patients. It was found that heavy isotopes of Zn and to an even greater extent Cu are enriched in erythrocytes relative to serum, while the difference is small for sulfur. Isotopic variations related to age and sex are relatively small. The 65 Cu/ 63 Cu ratio in the serum of patients with colon, breast, and liver cancer is conspicuously low relative to healthy subjects. The characteristic time over which Cu isotopes may change with disease progression (a few weeks) is consistent with both the turnover time of the element and albumin half-life. A parallel effect on sulfur isotopes is detected in a few un-medicated patients. Copper in liver tumor tissue is isotopically heavy. In contrast, Zn in breast cancer tumors is isotopically lighter than in healthy breast tissue. 66 Zn/ 64 Zn is very similar in the serum of cancer patients and in controls. Possible reasons for Cu isotope variations may be related to the cytosolic storage of Cu lactate (Warburg effect), release of intracellular copper from cysteine clusters (metallothionein), or the hepatocellular and biosynthetic dysfunction of the liver. We suggest that Cu isotope metallomics will help evaluate the homeostasis of this element during patient treatment, notably by chelates and blockers of Cu trafficking, and understand the many biochemical pathways in which this element is essential.